2016
DOI: 10.7812/tpp/16-017
|View full text |Cite
|
Sign up to set email alerts
|

Association of Unplanned Reintubation with Higher Mortality in Old, Frail Patients: A National Surgical Quality-Improvement Program Analysis

Abstract: Background: Unplanned postoperative reintubation increases the risk of mortality, but associated factors are unclear.Objective: To elucidate factors associated with increased mortality risk in patients with unplanned postoperative reintubation.Design: Retrospective study. Patients older than 40 years who underwent unplanned reintubation from 2005 to 2010 were identified using the American College of Surgeons National Surgical Quality Improvement Program database. Multiple regression models were used to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
(18 reference statements)
3
12
0
Order By: Relevance
“…This study reports a 1.6% incidence of unplanned postoperative reintubation (UPR), which is comparable to the range of 0.4%–4% reported by other studies [ [3] , [4] , [5] , [6] , [11] , [12] , [13] , [14] , [15] ]. Consistent with previous studies [ [1] , [2] , [3] , [4] , [5] , [6] ], the present study also identified UPR to be significantly associated with morbidity and mortality. UPR was associated with increased mortality, wound infection, postoperative RBC transfusion, prolonged hospitalization, pulmonary, renal, cardiac and thrombotic complications.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study reports a 1.6% incidence of unplanned postoperative reintubation (UPR), which is comparable to the range of 0.4%–4% reported by other studies [ [3] , [4] , [5] , [6] , [11] , [12] , [13] , [14] , [15] ]. Consistent with previous studies [ [1] , [2] , [3] , [4] , [5] , [6] ], the present study also identified UPR to be significantly associated with morbidity and mortality. UPR was associated with increased mortality, wound infection, postoperative RBC transfusion, prolonged hospitalization, pulmonary, renal, cardiac and thrombotic complications.…”
Section: Discussionsupporting
confidence: 92%
“…Unplanned postoperative reintubation (UPR) is therefore an unexpected event that indicates an unfavorable postoperative course. It serves as a marker for severe adverse outcome after surgery, and is associated significant morbidity, mortality and healthcare cost [ [1] , [2] , [3] , [4] , [5] , [6] ]. Indications for UPR have ranged from unexpected or failed extubation to clinical deterioration of patients after surgery [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“… 18 A patient's mFI is calculated as the number of variables present in a patient's medical history from the total 11 variables. 19 Patients with mFI scores ≥4 were grouped together to prevent variability associated with small group sizes. Patients without mFI variables were scored as 0 and included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Several strategies have the potential to minimize the high risk of unplanned reintubation in patients with morbid obesity and/or COPD, in turn associated with higher mortality, longer ICU course, increased incidence of nosocomial pneumonia and increased risk of transfer to long-term care facilities [ 165 168 ]. Incentive spirometry and aggressive chest physiotherapy should be instituted in the immediate postoperative stage [ 169 ].…”
Section: Minimizing the Risks Of Postoperative Reintubation In Neurosmentioning
confidence: 99%